A szerv- és szövetadományozás polgári jogi érvényesíthetõsége, avagy jogi szabályozásának ellentmondásai - Kiss, Nóra (Debreceni Jogi Műhely, 2006)
Developments in the last centuries in the fields of pharmacy and surgery have had a beneficial effect on the treatment of various diseases and injuries. As a result these two areas have attracted the support and admiration both of the scientific world and the general public.The examination of the effects of taking part by human beings has become unavoidable in the healing process. This relationship is unusually complex regards scientific opportunities and fragile in respect of people’s defencelessness.Important legal background material is available today relating to organ transplantations. It must be recognized, however, that this legal corpus has been a long time in the making and is still taking shape even today. Although people are trying to establish suitable legal framework for medical law, there are still some weak points and „prejudices”. Nowadays it is necessary to make an attempt at reconciling medical science and law not forgetting about the fact that their approaches are different.Medical law is not just about damages. Informing about the topic, the rights and the possibilities, preventing the trials: all of these things are more important. First of all, this is a life-saving procedure and money can not „repair” the problem in that case. Although it sounds cliché, it is true: you can not replace the unpurchasable organ by money. On the other hand, this should be a teamwork between the donors and recipients. They have to cooperate. The „job” of the law – which tries to be objective while it makes rules- should be to consider both views.It is well-known that the waitinglists are very long. What is the reason? What kind of solution is able to make the waiting-time shorter? These are very serious questions but the efficient transplantation is the most important. Transplantation is one thing and surviving it is another. And top of all that there is the problem of the „tragedy of the transplantation”: it is often said that donors have no rights. Which should/ can be preferred : the right to live or the right to voluntarism?! Can you decide which system (opt-in or opt-out donation system) gives better solution?!Giving a right answer is not so easy. Opt-out system may increase the level of available organs but it does not mean necessarily that there will be more organs for donation with absolute certainty. That is why you can not say simply that the „donor-licence” is a bad idea. There are lot of „ingredients” you should consider: technical developments, public education and last but not least social acceptance. According to the law in the opt-out system doctors should not ask the relatives about their opinions but it is said they usually do it. Is this an efficient system?!In my opinion an effective „dialogue” is needed -not only between law and medical science but between the organ donation systems, too- for the sake of a „flexible” legal background which can take part actively in our everydays in the 21st century.